'THE LAYER AND SCOPE OF LOANWORDS IN THE UZBEK LANGUAGE BASED ON ASQAD MUXTOR’S NOVEL “CHINOR” (International Conference on Economics, Finance, Banking and Management, 2025)
This article discusses the concept of loanwords, comparing the views of several scholars and analyzing the impact of such words on the language using Asqad Muxtor’s novel "Chinor" as an example.